German State Constitutional Courts: The Justices. Issue 2 (1st June 2021) - Reutter, Werner
Abstract: The article shows that two constitutional principles govern the election of justices and the composition of the 16 German state constitutional courts: democracy and the separation of powers. The recruitment of candidates, the vote on nominees in state parliaments, and the composition of benches of the courts in question support this assumption. There is no evidence indicating that a partisan takeover of German state constitutional courts has taken place. In addition, the majorities required for an appointment of justices of state constitutional courts seem less crucial than is often assumed.